Heterogeneity in plant population and species diversity in Barandabhar corridor forest, Chitwan - Shrestha, Binoj Kumar; Dangol, Dharma Raj; Ghimire, Krishnaji (Banko Janakari, 2008)
This paper presents spatial heterogeneity of the plant communities in terms of population and species diversity in the Barandabhar Corridor Forest, Chitwan. The study was carried out in 2000 in the northwestern part of the forest, adjacent to the local settlements. Standard quadrat sampling method was used for the study. Vegetation analysis showed that the Sal (Shorea robusta) dominated forest consisted of a total of 190 plant species. Among them, 7 species were in the canopy layer while 54 species were found in the middle layer and 183 species in the ground vegetation. The average density of plant communities of the canopy layer, middle layer and ground vegetation showed significant negative correlation (r = -0.67, r = -0.66 and r = -0.94 respectively) with the distance into the forest of plots from the outer part of the forest. The result concluded that the degree of degradation of the forest is higher in the core regions (Government forest area) than in the outer regions which lie within the community forest.Key words: Plant communities; Sal; density; species diversity; degradationBanko Janakari Vol.16(2) 2006 pp.58-63